2018
DOI: 10.1002/cncr.31634
|View full text |Cite
|
Sign up to set email alerts
|

Optimistic, realistic, and pessimistic illness perceptions; quality of life; and survival among 2457 cancer survivors: the population‐based PROFILES registry

Abstract: Optimistic IPs are associated with better HRQOL and survival, even if they may appear to be unrealistic with respect to cancer survivors' prognosis. Survivors with pessimistic IPs appear to have the worst outcomes. Therefore, efforts are needed to provide better support to patients with pessimistic IPs to improve their outcomes. Cancer 2018;124:3609-17. © The Authors. Cancer published by Wiley Periodicals, Inc. on behalf of American Cancer Society. This is an open access article under the terms of the Creative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 37 publications
2
20
0
Order By: Relevance
“…However, patient background may also profoundly affect physical and/or mental functional consequences or how these complications are perceived. This includes: advanced age (even if social impact may be greater in young patients) [34], comorbidity [35], socio-demographic disparities [36], personality traits [37], life style including tobacco use and weight gain [38]. Based on these considerations, we have compared most of these parameters between favorable (HRQoL > 50 at M24) and unfavorable groups (HRQoL ≤50 at M24).…”
Section: Discussionmentioning
confidence: 99%
“…However, patient background may also profoundly affect physical and/or mental functional consequences or how these complications are perceived. This includes: advanced age (even if social impact may be greater in young patients) [34], comorbidity [35], socio-demographic disparities [36], personality traits [37], life style including tobacco use and weight gain [38]. Based on these considerations, we have compared most of these parameters between favorable (HRQoL > 50 at M24) and unfavorable groups (HRQoL ≤50 at M24).…”
Section: Discussionmentioning
confidence: 99%
“…Results of two other PROFILES studies showed that illness perceptions may be associated with lower HRQoL and survival. 20,43 DTC patients' perceptions of their disease are thus important as they can influence health outcomes. A recent study on this same dataset showed that greater information support was associated with less threatening illness perceptions, and less threatening illness perceptions were in turn associated with less distress.…”
Section: Distress and Illness Perceptions In Thyroid Cancer 379mentioning
confidence: 99%
“…How patients perceive their illness is a known determinant of HRQoL in various patient groups including cancer. [11][12][13] These illness perceptions are hypothesized to influence illness adaptation and outcomes within the structure of the common-sense self-regulation model (SRM) of illness. 14 According to the SRM model, when individuals are faced with an illness, they form cognitive representations (beliefs about the illness) and emotional reactions which together affect both physical and psychosocial outcomes, principally through coping responses.…”
Section: Introductionmentioning
confidence: 99%
“…14 Previous studies among various cancer populations not including DTC, demonstrated that cancer survivors with optimistic illness perceptions regarding their prognosis had better health outcomes compared to those with pessimistic and realistic Illness perceptions. 13 Among various malignancies (breast, prostate, and colorectal cancer) negative illness perceptions were related to poorer HRQoL. 15,16 Furthermore, previous studies provide promising evidence for the effectiveness of interventions aimed at helping these individuals acquiring more adaptive illness perceptions, thereby improving their HRQoL.…”
Section: Introductionmentioning
confidence: 99%